Effect Of Different Techniques Of Acidification By Sauerkraut Extracts To Physical Performance Of Acidified Fish Meal - B. Sulistiyanto; C.S. Utama; K. Nugoho (JURNAL KESEHATAN, 2009)
Abstract Research to obseme effect of diferent techniques o/ acidification by sauerkraut extracts to physicorganoleptically performance of acidified fish meal has been conducted in the Laboratory of Feed Technologt Faculty of Animal Science Diponegoro University. Extract of Sauerkraut is made by fermenting wastes of vegetable market (LPS) for 6 days, which is Etarting by molasses. Acidification of Wish by extract solution of LPS was conduct by dipping/or 0, 4 and 8 hours, and dippingfollowed by ensilingfor l0 days. Changes in pH, odor, color, texture and moisture content of acidified fish meal is parameters obsemed. Results of research indicate that the extract LPS can be used in the acidification of